ПЬЕСЫ МАЛОЙ ФОРМЫ В КЛАССЕ “ОБЩЕГО ФОРТЕПИАНО” - Рахимова , Нигина (Educational Research in Universal Sciences, 2024)
This article describes how to transfer to students a complex of performing skills and abilities, teach them the ability to work on a cantilena, a master class for the professional performance of highly artistic forms of piano literature, and also increase the level of their professional and artistic training. A step-by-step method of learning small-form pieces is used: learning fragments of pieces at a slow tempo, including jazz pieces, using legato, cantabile, pedaling, sound techniques in the process of learning, introducing them to more successful mastery of various types of piano techniques, a gradual transition to learning more complex ones forms . Teaching students the ability to hear and evaluate their performance, sensing the relationship between real sound and musical-auditory concepts.